Neoadjuvant ipilimumab plus nivolumab therapy as a potential organ preservation strategy in mucosal melanoma: case report - Ong, Claire V.; Samlowski, Wolfram (Frontiers in Oncology, 2024)
Mucosal melanoma represents an uncommon melanoma subtype. Wide excision has long represented the standard therapeutic approach. Unfortunately, there is a high relapse rate and mortality. Neoadjuvant therapy with ipilimumab plus nivolumab has shown significant activity in cutaneous melanoma. We present two cases of mucosal melanoma, each with potential regional dissemination, who were treated with neoadjuvant immunotherapy with minimal toxicity. Both patients were closely monitored and achieved radiologic and pathologic complete responses. These patients were able to avoid radical surgery and related functional consequences. Both patients remain recurrence-free with protracted follow-up. The potential usefulness of neoadjuvant immunotherapy as an organ preservation strategy in mucosal melanoma deserves further evaluation in prospective clinical trials. Immunotherapy using immune checkpoint inhibitor (ICI)-directed antibodies has become an increasingly important treatment option for cutaneous melanoma in recent years. Commonly used ICIs include ipilimumab, an antibody against cytotoxic T lymphocyte antigen 4 (CTLA4). Also, nivolumab and pembrolizumab, monoclonal antibodies against programmed death-1 (PD1) have shown clinical activity (11). Combination therapy using CTLA4 and PD1 antibodies together in cutaneous melanoma has produced further increases in progression-free and overall survival, albeit with increased risk of toxicity ( 12).Recently, a pre-operative (neoadjuvant) treatment approach has shown significant promise in regionally advanced cutaneous melanoma. In a pair of phase II studies, this approach has yielded a high percentage of patients who achieved a pathologic complete response or near complete response (13,14). Patients with virtually complete pathologic responses also appeared to benefit with a very high rate of progression-free survival. In a more recent SWOG 1801 randomized clinical trial, resectable stage III or IV cutaneous melanoma patients were randomized to receive either neoadjuvant pembrolizumab followed by adjuvant therapy or post-surgical adjuvant pembrolizumab. In this trial, the 2-year event-free survival in the neoadjuvant-adjuvant group was significantly higher than that of the adjuvant-only group, 72% compared to 49% (15). These results strongly suggest that neoadjuvant therapy improves outcomes in locoregionally advanced cutaneous melanoma.